Analisis Kontribusi Sektor Unggulan Terhadap Pertumbuhan Ekonomi di Kota Solok - Intan Putri Wahyuni Firhad; Tartila Devy; Amsah Hendri Doni; Rahmi Isriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify leading sectors and analyze their contribution to economic growth in Solok City during the 2019–2024 period. Economic growth is a crucial indicator for measuring the success of a region's development. As a strategic location in West Sumatra Province, Solok City possesses significant economic potential, particularly in the agriculture, trade, and transportation sectors. These sectors have long been the mainstays of Gross Regional Domestic Product (GRDP). However, the dynamics of global and local economic change demand empirical analysis to identify which sectors are truly superior, possessing competitiveness and long-term development potential. This study aims to identify leading sectors and analyze their contribution to Solok City's economic growth to ensure more effective and sustainable regional development. This study uses a quantitative descriptive approach utilizing secondary data from the Central Statistics Agency (BPS) of Solok City and West Sumatra Province for the 2019–2024 period. The analytical methods employed include the Location Quotient (LQ), Dynamic Location Quotient (DLQ), and the Klassen Typology. These three methods are used in an integrated manner to measure sectoral contributions, assess growth prospects, and map the position of Solok City's economic sectors within the regional context. The research results show that the trade and transportation sectors are basic and prospective, indicated by LQ and DLQ values greater than one. The agricultural sector continues to contribute significantly, despite its slowing growth. Strengthening leading sectors through modernization, infrastructure development, and cross-sector integration is essential to achieve inclusive and sustainable economic growth in Solok City.